EVALUASI PROGRAM PEMBELAJARAN MEMBACA AL QUR’AN METODE AL QALAM DENGAN MODEL EVALUASI ROI (Studi di Pesantren Lansia ‘Habibi Ainun’ Puuwatu Kota Kendari) - Erni Qomariyah; Aris Try Andreas Putra (Journal Publicuho, 2023)
The purpose of this writing is to evaluate the Qur'an reading learning program using the Al Qalam Method. This program is a collaboration between the Al Qalam Education Foundation and Rumah Zakat by creating the Rumah Qur'an Lansia Pesantren Lansia program 'Habibi Ainun' which is located in Watulondo Village, Puwatu District, Kendari City. The results showed that the Al Qalam Education Foundation did not spend any learning program costs at all. So for the foundation, this program is very beneficial because it helps achieve the foundation's mission, which is to contribute to instilling Islamic values for the people of Kendari City. As for when viewed from Rumah Zakat, Kendari Branch is also beneficial and provides benefits because of the 30 learners, as many as 18 people can attend the graduation of the Al Qalam Method. The 12 people who have not graduated will still be given learning by participants from mothers who have graduated and graduated without spending any more money